Tentative Identification of Compounds, Antioxidant, and Antimicrobial Activity of the Edible Part of Benincasa hispida L. fruit (Cucurbitaceae) - Carla Wulandari Sabandar; Harni Sartika Kamaruddin; Reskiya Nur Insani; Rana Triana Amin; Zulkifli Zulkifli; Tien Tien (Borneo Journal of Pharmacy, 2023)
The edible part of Benicasa hispida (Thunb.) Cogn. fruit is traditionally used in Southeast Sulawesi to treat high blood pressure, typhoid fever, and body cooling. The present study evaluated the chemical compounds present in the 80% ethanol of the edible part of the plant using phytochemical screening and an LC-MS analysis, antioxidant activity based on assays on total phenolics content (TPC), total flavonoids content (TFC), and DPPH, and antimicrobial activity towards Salmonella typhi, Escherichia coli, Staphylococcus aureus, and Candida albicans. Phytochemical screening revealed the presence of tannins, flavonoids, terpenoids, steroids, and saponins in the extract. As many as eighteen compounds (1-18) were tentatively identified in the extract, including sugars, a simple phenolic, a tricarboxylic acid, a peptide, flavonoids, quinic acid derivatives, phytosterols, triterpenoids, and saponins. The extract exhibited remarkable antioxidant activity with an SC50 value of 23.4 µg/mL, although its TPC (1.1±0.1 mg GAE/g extract) and TFC (1.0±0.1 mg QE/g extract) values were considered in low amounts. The extract was found inactive to inhibit the microbial growths of all tested microbes. However, raffinose (3) present in the extract might be beneficial as a prebiotic to promote a healthy human gut. The study concludes that the 80% ethanol extract of the edible part of B. hispida fruit could be used to develop natural antioxidant agents and nutraceuticals.